The role of Rabi splitting tuning in the dynamics of strongly coupled J-aggregates and surface plasmon polaritons in nanohole arrays. Issue 27 (28th June 2016) - Wang, Hai; Toma, Andrea; Wang, Hai-Yu; Bozzola, Angelo; Miele, Ermanno; Haddadpour, Ali; Veronis, Georgios; De Angelis, Francesco; Wang, Lei; Chen, Qi-Dai; Xu, Huai-Liang; Sun, Hong-Bo; et al.
Abstract : Rabi splitting tuning in strongly coupled J-aggregates/surface plasmon polaritons systems. Abstract : We have investigated the influence of Rabi splitting tuning on the dynamics of strongly coupled J-aggregate/surface plasmon polariton systems. In particular, the Rabi splitting was tuned by modifying the J-aggregate molecule concentration while a polaritonic system was provided by a nanostructure formed by holes array in a golden layer. From the periodic and concentration changes we have identified, through numerical and experimental steady-state analyses, the best geometrical configuration for maximizing Rabi splitting, which was then used for transient absorption measurements. It was found that in transient absorption spectra, under upper band excitation, two bleaching peaks appear when a nanostructured polaritonic pattern is used. Importantly, their reciprocal distance increases upon increase of J-aggregate concentration, a result confirmed by steady-state analysis. In a similar manner it was also found that the lifetime of the upper band is intimately related to the coupling strength. In particular, we argue that with strong coupling strength, i.e. high J-aggregate concentration, a short lifetime of the upper band has to be expected due to the suppression of the bottleneck effect. This result supports the idea that the dynamics of hybrid systems is profoundly dependent on Rabi splitting.